TINJAUAN YURIDIS TERKAIT KEPASTIAN HUKUM HAK PERTANAHAN DAN JAMINAN FIDUSIA BAGI PEMEGANG IZIN PEMAKAIAN TANAH DI KOTA SURABAYA - Elysia Arianti Dewi; Suyatno Suyatno; Fajar Rachmad Dwi Miarsa; M. Zamroni; Ahmad Heru Romadhon (LPPM Universitas Ekasakti Padang, 2023)
The objectives of this study are to: (1) determine the best course of action for the Municipality of Surabaya's Ijo Letter owners in terms of legal certainty so that they can transfer land rights in the future with minimal formalities and at market rates; and (2) conduct a legal analysis pertaining to the terms of fiduciary guarantees and their relationship to the position of IPT as collateral for immovable tangible objects. This kind of study employs normative legal research. The data analysis used is qualitative analysis, which entails examining data derived from legal sources in accordance with doctrines, theories, rules and regulations, laws and principles, expert opinions, or the researchers' own ideas. The study's findings revealed that: (1) IPT (Land Use Permit) or Letter Ijo are permits unrelated to agrarian reform, and in accordance with national land law, which upholds the principle of horizontal separation, the Surabaya City Government is legally in possession of land rights with management rights from the State, while IPT holders are the owners of buildings that have been built on the land. (2) Only the building is authorized as a fiduciary assurance on property having IPT status and complying to the horizontal separation concept. This is in accordance with Surabaya Regional Regulation 3/2016 article 7 letter (c) and the evaluation of structures erected on land with assured IPT status based on their legal standing and future market potential